Effective Use of Television to Popularize Science - Richardson, Jacques G. (Journal of Technical Writing and Communication, 1978)
The growing use of television to popularize science and technology has generated a trial examination of the motives, the dynamics, and the effectiveness of the process. Some results of the first international meeting held on the subject are presented by one of the participants.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC80YzJuLTU1eDYtOXIwMy03eTE5